Chatbot for Career Guidance Using AI - Ohm, Akshansh; Bhavani , K (International Journal of Computer Sciences and Engineering, 2019)
Chatbots are computer programs that simulate intelligent human conversation. The development and creation of new applications have been possible because of the design and production of interactive chatbots that help in a better way for the progress of the people. This project will describe current efforts in the development of an intelligent Career Counselling Bot. Career counselling project is built using artificial intelligence algorithms that are used for analyzing user’s queries and understand the user’s message. It provides some valid result to the query of the user. The User can query any career related queries through the system. The user does not have to personally go to a career counsellor for the same. The System analyses the question and then answers to the query as if it is answered by the counsellor. This system helps the user to choose the right career that they should follow according to their interests and capabilities.